Construction and application of the three-level storage information system in the management of low-cost surgical consumables (手术室低值耗材三级库信息化管理模式的构建及应用) - XU Ying (许瑛); YANG Lijun (杨利君); MENG Yuehua (孟月华); LIU Lin (柳琳); ZHANG Lianen (张怜恩) (中西医结合护理)
Objective To evaluate the three-level storage information system in the management of low-cost surgical consumables. Methods The standard information module for various kinds of low-cost surgical consumables was established, and essential data of low-cost surgical consumables in each operation unit was determined. The materials requisition form will be filled by surgical nurses according to the standard information module and actual demands, and low-cost surgical consumables will be distributed in a regulative and convenient way. Results Time spent in preparing and supplying low-cost surgical consumables and interval time between two operations were reduced after implementation of three-level storage information system (P＜0. 05). The on-duty rate of the circulating nurse increased from 83. 04% to 85. 82%. ConclusionThree-level storage information system is an effective tool in the management of low-cost surgical consumables, which is designed to ensure the safety of surgery and improve the efficiency and quality of work in the operation room. (目的 探讨三级库信息化管理模式在手术室低值耗材使用管理的应用效果。方法 运用电子信息技术, 建立各类手术低值耗材信息化标准模块, 并确立每个手术间各类低值耗材基础数。手术间护士依据各类手术低值耗材标准化模块以及实际消耗的品种、数量制成电子请领清单向无菌耗材库请领, 实现规范、快捷配送至手术间, 保证手术配合质量和工作效率。结果 应用信息系统对手术室低值耗材使用实行三级库管理后, 低值耗材准备时间、低值耗材供应时间、连台手术衔接时间均少于应用前(P＜0. 05)。巡回护士在位率由应用前的83. 04%提升至应用后的85. 82%。结论 采用三级库信息化管理模式对手术室低值耗材进行管理, 可确保手术安全, 有效提高工作效率和工作质量, 为手术室高效运转提供良好保障。)